2023
DOI: 10.7759/cureus.37380
|View full text |Cite
|
Sign up to set email alerts
|

School-Based Stroke Education Through On-Demand E-learning During Coronavirus Disease 2019 Pandemic: Itoigawa Stroke Awareness Campaign

Abstract: IntroductionRaising stroke awareness is important to shorten the interval from onset to consultation. We performed a school-based stroke education by on-demand e-learning during the coronavirus disease 2019 pandemic. MethodsWe performed on-demand e-learning and distributed the online-and paper-based manga about stroke for students and parental guardians in August 2021. We carried out this in a manner similar to the prior effective online stroke awareness initiatives in Japan. An online post-educational survey … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
(46 reference statements)
0
0
0
Order By: Relevance
“…Social media-based campaigns using advertisements provide feasibility and cost-effectiveness to raise stroke awareness in the general population [20]. Such campaigns can be particularly effective during pandemic disasters like the coronavirus disease 2019 pandemic, with lower costs compared to in-person or paper distribution methods [21]. Our study revealed a higher proportion (47%) having good stroke awareness compared to a previous study of Thai patients during 2010-2011, which found that only one-third of patients with a stroke were aware of stroke symptoms [9].…”
Section: Discussionmentioning
confidence: 99%
“…Social media-based campaigns using advertisements provide feasibility and cost-effectiveness to raise stroke awareness in the general population [20]. Such campaigns can be particularly effective during pandemic disasters like the coronavirus disease 2019 pandemic, with lower costs compared to in-person or paper distribution methods [21]. Our study revealed a higher proportion (47%) having good stroke awareness compared to a previous study of Thai patients during 2010-2011, which found that only one-third of patients with a stroke were aware of stroke symptoms [9].…”
Section: Discussionmentioning
confidence: 99%